Efektivitas Perjanjian Kerja Laut Sebagai Syarat Kelaiklautan Dan Kesejahteraan Anak Buah Kapal Indonesia - Hadijah Hadijah; Dian Lieska; Yulinda Yusar (Institut Transportasi dan Logistik Trisakti, 2020)
Safety is one of the conditions that should be met for a ship to be seaworthy. Besides safety, the welfare of the ship’s crew (ABK) should be guaranteed. The aim of this research is to provide input to the Ministry of Transportation about the welfare conditions of ship’s crew on Indonesia flag state. The data analysis method used in this study was qualitative, means that the data collected was based on the problem on-board, in the form of a questionnaire to 400 Indonesian ship’s crew of Indonesian ships (size 300 GT above domestic shipping and size 500 GT above foreign shipping). The results of the analysis shows that the need for improvement of the Ship’s Articles documents in accordance with admiralty/nautical laws which are the ship’s crew gets salary without any benefits, the average work exceeds the specific working hours, minimum accommodation facilities, unfulfilled full compliment of health insurance and employment, as well as the absence of compliance with national sea transportation companies to fulfill the contents of the ship’s articles.